1999
DOI: 10.1042/bj3430505
|View full text |Cite
|
Sign up to set email alerts
|

The malonyl-CoA–long-chain acyl-CoA axis in the maintenance of mammalian cell function

Abstract: Long-chain acyl-CoA esters have potent specific actions (e.g. on gene transcription, membrane trafficking) as well as non-specific ones (e.g. on phospholipid bilayers). They are synthesized on the cytosolic aspects of several intracellular membranes, to give rise to (a) cytosolic pool(s) to which a variety of enzymes and processes have access, including some localized in the nucleus. Their concentration in cells is highly regulated, interconversion with corresponding acylcarnitines being the most important mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 143 publications
(161 reference statements)
1
67
0
Order By: Relevance
“…We showed recently that, in the heart, acetyl-CoA derived from the partial peroxisomal β-oxidation of long-chain and very-longchain fatty acids is used for malonyl-CoA synthesis [4], a key regulator of the mitochondrial oxidation of long-chain fatty acids [5,6]. This conclusion was based on the comparison of the 13 Clabelling of malonyl-CoA and the acetyl moiety of citrate, a proxy for mitochondrial acetyl-CoA [4].…”
Section: Introductionmentioning
confidence: 99%
“…We showed recently that, in the heart, acetyl-CoA derived from the partial peroxisomal β-oxidation of long-chain and very-longchain fatty acids is used for malonyl-CoA synthesis [4], a key regulator of the mitochondrial oxidation of long-chain fatty acids [5,6]. This conclusion was based on the comparison of the 13 Clabelling of malonyl-CoA and the acetyl moiety of citrate, a proxy for mitochondrial acetyl-CoA [4].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is suggested that the interplay between the effects of the structural motifs on either side of the turn predicted for residues 15-19 (TPDG, see above) enables L-CPT I to respond to changes in the fluidity of the membrane in which TMs 1 and 2 are embedded, and with/ within which they are presumed to interact (7,11,22,27).…”
Section: Table II Comparison Of Activities and Kinetic Parameters Formentioning
confidence: 99%
“…CPT-1 is an integral mitochondrial membrane protein that catalyzes the esterifcation of long-chain acyl-CoAs to L-carnitine, which is the rate-limiting step in the transport of these acyl moieties from the cytosol into the mitochondria, where they undergo fatty acid oxidation (20). CPT-1 is sensitive to inhibition by malonyl-CoA, which is important for signaling the availability of fuels (42), (43). In mammals, CPT-1 exists as two isoforms, liver and muscle (L-CPT-1 and M-CPT-1, respectively), that are similar in sequence but differ kinetically with respect to their malonyl-CoA sensitivities and K m values for carnitine (44), (45).…”
Section: C75 Inhibits Fas and Stimulates Cpt-1 And Fatty Acid Oxidatimentioning
confidence: 99%